Regularities in Changing Magnetic Intensity Passing Through Electric Conduction Objects - V. V. Pavliouchenko; E. S. Doroshevich (Наука и техника)
The presented experimental data have made it possible to determine  some rules in time changing of a normal magnetic intensity component depending on the position of an object edge relative to the source axis and object size. The paper considers the case when the magnetic field of the linear initial source passes through electric conduction objects.